FREQUENCY OF PRESENTATION OF LUMBOSACRAL INSTABILITY IN LABRADOR RETRIEVER DOGS - Arana C., Dennis (2013)
The aim of the study was to determine the frequency of lumbosacral instability in Labrador Retriever dogs older than six months of age, and to determine its association with the variables sex, age, body weight, radiological signs, and clinical signs of lumbosacral pain. The disease was detected by radiographic evaluation. Sixty dogs were randomly selected and distributed according to sex (30 per sex), age (3 groups) and body weight (3 categories). The frequency of lumbosacral instability was 75.0% (45/60). The females were most affected (86.7%, 26/30) and male:female ratio was 1:1.4. None statistical association was found due to age. Obese animals (>15% overweight on the limit of the standard) showed greater frequency (87.5%, 21/24). The most frequent radiological sign was the ventral subluxation of the sacrum relative to L7 (75.0%, 45/60). Transrectal palpation allowed the highest detection of lumbosacral pain (80.0%, 45/60). The radiological evaluation of the disease showed a high degree of concordance with the evaluation of the lumbosacral pain (p<0.05).